2002
DOI: 10.2214/ajr.179.5.1791179
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Core Needle Biopsy of Radial Scars of the Breast: When Is Excision Necessary?

Abstract: . Diagnosis of radial scar based on core needle biopsy is likely to be reliable when there is no associated atypical hyperplasia at percutaneous biopsy, when the biopsy includes at least 12 specimens, and when mammographic findings are reconciled with histologic findings. When the lesion diagnosed by core needle biopsy as radial scar does not meet these criteria, excisional biopsy is indicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
113
4
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 208 publications
(124 citation statements)
references
References 31 publications
5
113
4
2
Order By: Relevance
“…These are more likely to be incidental in nature and their management is most controversial. The mean size of radial scars in our series was 3.11 mm, while those in other reports 3,5,7,8,11,17,18 range in size from 1 mm up to 5.0 cm. This wide range in sizes is a result of variability of inclusion criteria among different studies.…”
Section: Commentcontrasting
confidence: 68%
See 2 more Smart Citations
“…These are more likely to be incidental in nature and their management is most controversial. The mean size of radial scars in our series was 3.11 mm, while those in other reports 3,5,7,8,11,17,18 range in size from 1 mm up to 5.0 cm. This wide range in sizes is a result of variability of inclusion criteria among different studies.…”
Section: Commentcontrasting
confidence: 68%
“…In most studies, the rate of upgrade, or underestimation of malignancy, of surgically excised radial scars has been variable, but most reported rates are in the range of 0% to 10%. 3,[5][6][7][8][9][10][11][12][13][14] However, most radiologists are not comfortable recommending clinical follow-up over surgical excision of radial scars because studies have not consistently demonstrated an upgrade rate of less than 2%, the cutoff for categorizing a lesion as ''probably benign'' according to the BI-RADS (Breast Imaging Reporting and Data System) system (BI-RADS 3). 15 The variability in reported upgrade rates may be due to several factors including variability in study design, small sample sizes, and inconsistent radiologic-pathologic concordance.…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…The biopsy type, the volume of the sample and the experience of the operator can all affect the accuracy of a core needle biopsy (21)(22)(23)(24). Core needle biopsies can be sufficient for the diagnosis of small spiculated lesions such as focal architectural distortions or radial sclerosing lesions (25,26). In this study, all microcalcification clusters and most of the focal architectural distortion areas and spiculated lesions were surgically excised after needle wire localization to guarantee sample adequacy and to prevent possible problems related to poor localization.…”
Section: Core Needle Biopsy Cases Study Group (41)mentioning
confidence: 99%
“…36 In some centres, however, the imaging suggestion of a radial scar is followed by surgical excision without pre-operative CNB.…”
Section: Radial Scarmentioning
confidence: 99%